The Corporate Conception of the State and the Origins of Limited Constitutional Government - Eric Enlow (Washington University Journal of Law & Policy, 2001)
This Essay discusses the corporate conception of the state in European and American legal history.
Keywords: Corporations; Popular sovereignty; Constitutionalism; Constitutional history – United States; Constitutional history – Europe; Representative government